Networked learning in a postdigital-biodigital age - Jandri´ć, Petar; Hayes, Sarah (Proceedings of the International Conference on Networked Learning, 2024)
Networked Learning has developed predominantly in university / research settings and communities, yet much of the research across decades can be shown to have implicit links with current popular and much broader global concepts, such as bioinformation, biodigitalism, postdigitalism, and viral modernity. In this paper we explore these implicit connections as an important and perhaps less unrecognized part of Networked Learning. We therefore seek to surface some postdigital-biodigital challenges in Networked Learning by revisiting relevant histories, concepts, and definitions and also noticing where there are parallels and connections, particularly when Networked Learning and Postdigital Science and Education have developed in the same Zeitgeist. Despite radically different histories, these areas of research seem to have resulted in different, yet often overlapping theories, research approaches, and ethos. After taking time to look into a number of these cross-cutting areas of interest, we ask the question of why a focus towards postdigital-biodigital challenges in Networked Learning is worthwhile, and indeed, why now? Based on our explorations we perceive Networked Learning to implicitly hold a long history of deep and successful engagement with postdigital-biodigital challenges in theory and through the concept of convergence. The role of convergence is an important and sustained concept in Networked Learning that can help in breaking down perceived barriers to developing cross-cutting research in any of the areas discussed throughout this paper. It is therefore timely to bring to light explicitly such connections, to help us to focus our research efforts on Networked Learning in a postdigital-biodigital age.